Reactions to environmental allergens in cats with feline lower airway disease - Hartung, Birte F.; Mueller, Ralf S.; Gauss, Jana; Weitzer, Tamara; Boehm, Teresa M. S. A.; Palić, Jelena; Schulz, Bianka (Frontiers in Veterinary Science, 2023)
Objectives: Aeroallergens have been discussed as potential triggers for feline asthma (FA), which can be induced experimentally by allergen sensitization. To date, only few studies have investigated reactions to environmental allergens in cats with naturally occurring feline lower airway disease (FLAD). The aim of the study was to compare results of intradermal testing (IDT) and serum allergen-specific immunoglobulin E-(IgE) testing (SAT) in cats with FLAD, and to investigate possible associations with allergen exposure.Material and methods: Eight cats with eosinophilic airway inflammation (EI), ten cats with mixed inflammation (MI), six with neutrophilic inflammation (NI), and 24 healthy cats (HC) were included. Cats diagnosed with FLAD were assigned to the different inflammatory groups based on bronchoalveolar lavage fluid (BLAF) cytology. SAT was performed in all cats; IDT was only carried out in cats with FLAD. Information about the cats' environment and potential allergen exposure was obtained using an owner questionnaire.Results: In comparison to 83% of HC with positive reactions on SAT only 52% of cats with FLAD had positive responses (p = 0.051). Significantly more positive reactions per cat were detected on IDT than on SAT (p = 0.001). No significant difference was found for positive reactions per cat on SAT when compared between HC, NI, EI, and MI (p = 0.377). Only "slight" agreement was found for most allergens when reactions obtained in both tests in cats with FLAD were compared, except for "moderate" agreement for English plantain (k = 0.504) and Alternaria alternata (k = 0.488). Overall, no clear association between the cats' environment and allergen reactions were detected.Conclusions and clinical importance: Interpretation of allergy test results in cats with FLAD should be done in the context of clinical signs and individual factors.